Enabling knowledge creation : how to unlock the mystery of tacit knowledge - Von Krogh, Georg (OUP OxfordGB, 2000)
Presents knowledge enabling as a 5-step process which can enhance the knowledge-creating potential of an organization. Identifies the 5 knowledge enablers as: instilling a knowledge vision; managing conversations; mobilizing knowledge activists; creating the right context; and, globalizing local knowledge. Provides guiding principles, and strategies etc. for promoting knowledge creation, and uses case stories of successful companies to support this approach.